Cell reprogramming by 3D bioprinting of human fibroblasts in polyurethane hydrogel for fabrication of neural-like constructs. (1st April 2018) - Ho, Lin; Hsu, Shan-hui
Graphical abstract: Abstract: 3D bioprinting is a technique which enables the direct printing of biodegradable materials with cells into 3D tissue. So far there is no cell reprogramming in situ performed with the 3D bioprinting process. Forkhead box D3 (FoxD3) is a transcription factor and neural crest marker, which was reported to reprogram human fibroblasts into neural crest stem-like cells. In this study, we synthesized a new biodegradable thermo-responsive waterborne polyurethane (PU) gel as a bioink. FoxD3 plasmids and human fibroblasts were co-extruded with the PU hydrogel through the syringe needle tip for cell reprogramming. The rheological properties of the PU hydrogel including the modulus, gelation time, and shear thinning were optimized for the transfection effect of FoxD3 in situ . The corresponding shear rate and shear stress were examined. Results showed that human fibroblasts could be reprogrammed into neural crest stem-like cells with high cell viability during the extrusion process under an average shear stress ∼190 Pa. We further translated the method to the extrusion-based 3D bioprinting, and demonstrated that human fibroblasts co-printed with FoxD3 in the thermo-responsive PU hydrogel could be reprogrammed and differentiated into a neural-tissue like construct at 14 days after induction. The neural-like tissue construct produced by 3D bioprinting from human fibroblasts may be applied to personalized drug screening or neuroregeneration. Statement of Significance: There is no study so far on cell reprogramming in situ with 3D bioprinting. In this manuscript, a new thermoresponsive polyurethane bioink was developed and employed to deliver FoxD3 plasmid into human fibroblasts by the extrusion-based bioprinting. When the polyurethane gel was extruded through the syringe tip, the shear stress generated may have caused the transient membrane permeability for transfection. The shear stress was optimized for transfection in situ by 3D bioprinting. We demonstrated that human fibroblasts could be reprogrammed into neural crest-like stem cells by 3D bioprinting with the gel, and the reprogrammed cells underwent neural differentiation in the printed structure after induction. The neural-like tissue engineering constructs fabricated by 3D bioprinting from human fibroblasts may be applied for neuroregeneration or further developed as mini-brain for basic research and drug screening.